A contextualidade da interferência condicional de dois fótons: um estudo em múltiplos cenários - Gilberto Ferreira Borges Júnior (2013)
In this work we test a family of noncontextuality inequalities developed from a unied view of several non-contextual scenarios, ie, a construction that allows unify seemingly disparate Gedankenexperiments used for quantum contextuality proofs, among which is the experiment that allows testing the CHSH inequality. Each of these inequalities predicts numerical limitations on the correlations of a physical system, when they are modeled by noncontextual theories. Violation of these inequalities shows that for a given scenario the correlations in the system can not be explained from a noncontextual viewpoint . The system which we want to test the contextual nature is two photonic qbits in the transversal path variable of twin photons generated by Spontaneous Parametric Down Conversion (SPDC). After being generated, the photon pairs cross a double-slit and exit it in a entangled state in path variables. Violation of the non-contextual inequalities for different measurement scenariosdemonstrates that the nonlocal conditionality displayed in the Youngexperiment with photons generated by SPDC, can not be properly explained by a local deterministic model, i.e, can not be explained in scope of a non-contextual hidden variable theory.